Enhancing Hate Speech Detection: Addressing Data Quality, Annotation Bias, Contextual Understanding, and Dynamic Adaptation (International Journal of Food and Nutritional Sciences, 2022)
Hate speech detection in online platforms has become a critical concern in recent years, as it poses serious threats to social cohesion and the well-being of individuals. This research focuses on enhancing the effectiveness of hate speech detection by addressing four major challenges: data quality, annotation bias, contextual understanding, and dynamic adaptation.Firstly, the issue of data quality is addressed through the development of robust methodologies for collecting and curating high-quality training datasets, minimizing noise and biases. Annotation bias is tackled by exploring innovative techniques to mitigate the subjectivity of human annotators, ensuring more accurate and unbiased labeling.Secondly, the research delves into the complexities of contextual understanding, aiming to create machine learning models that can decipher nuanced language, sarcasm, and cultural references. These models enable a deeper comprehension of hate speech in its diverse forms across various languages and communication modalities, including text, images, and videos. Lastly, recognizing the dynamic and evolving nature of hate speech, the study focuses on developing adaptive algorithms that continuously learn and adapt to emerging hate speech patterns, keeping pace with the ever-changing landscape of online discourse. This research seeks to significantly improve hate speech detection, contributing to a safer and more inclusive digital environment by addressing these pressing challenges and advancing the state-of-the-art in automated hate speech detection technology.